104k views
1 vote
Simplify the polynomial expression.
3x(-2x+7)-5(x-1)(4x-3)

2 Answers

1 vote

Answer:
-26x^2+56x-15

Explanation:

The first step is to apply Distributive property.

You also need to remember the Product of powers property, which states the following:


(a^m)(a^n)=a^((m+n))

Applying these properties:


3x(-2x+7)-5(x-1)(4x-3)=\\=-6x^2+21x-5(4x^2-3x-4x+3)\\=-6x^2+21x-20x^2+15x+20x-15

And finally, you need to add the like terms.

Therefore, you get:


=-26x^2+56x-15

User Laurynas Biveinis
by
5.1k points
4 votes

Answer:

The simplified form is -26x^2 + 56x -15

Explanation:

We need to solve the expression:

3x(-2x+7)-5(x-1)(4x-3)

Multiplying the terms outside the bracket with the terms inside the bracket.

=-6x^2+21x-5(x(4x-3) -1(4x-3))

= -6x^2+21x-5(4x^2-3x-4x+3)

= -6x^2+21x-5(4x^2-7x+3)

Now multiply -5 with the terms inside the bracket

= -6x^2+21x -20x^2 +35x -15

Now, Combining the like terms:

= -6x^2 -20x^2 +21x+35x -15

Adding the like terms

= -26x^2 + 56x -15

So, the simplified form is -26x^2 + 56x -15

User Christophe P
by
6.3k points